1975
DOI: 10.1007/bf00689565
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of methyl mercury salts on the rabbit nervous system

Abstract: Young adult rabbits have been given methyl mercury salts by subcutaneous injections or by gastric intubation. After 3 daily doses of 7.5 mg/kg by the 8th day moderate to severe ataxia developed, and after 4 doses, severe ataxia. Some of these latter animals might die. This species, therefore, seems to be about twice as sensitive to the neurotoxic properties of methyl mercury salts as the laboratory rat. With the light microscope extensive degenerative changes were seen in primary sensory ganglion cells, in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In the present study, although neuronal cell death was distributed widely in the central and peripheral nervous systems, calcium deposits, as detected by staining with von Kossa's method, were restricted to the cerebellum from day 32 onward. In contrast calcium deposition has never been reported, even in chronic cases of human MeHg intoxication 12 or in experimental MeHg intoxication in the mouse, 16 rabbit 15 or cat. 14 It is likely that cerebellar calcification (detected by von Kossa's method) following MeHg intoxication and dimethyl mercury exposure is specific to the rat.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the present study, although neuronal cell death was distributed widely in the central and peripheral nervous systems, calcium deposits, as detected by staining with von Kossa's method, were restricted to the cerebellum from day 32 onward. In contrast calcium deposition has never been reported, even in chronic cases of human MeHg intoxication 12 or in experimental MeHg intoxication in the mouse, 16 rabbit 15 or cat. 14 It is likely that cerebellar calcification (detected by von Kossa's method) following MeHg intoxication and dimethyl mercury exposure is specific to the rat.…”
Section: Discussionmentioning
confidence: 91%
“…It is well known that the nervous system displays regional and cellular differences in its sensitivity to MeHg. 7,8 The cerebellar granule cells, calcarine cortical neurons, and the dorsal root ganglion (DRG) neurons in humans [9][10][11][12] and in other animals [13][14][15][16][17][18][19][20] are the most vulnerable to MeHg. Previous histopathologic studies using von Kossa's staining method have shown that deposition of calcospherites occurs in the granular layer of the cerebellum in rats that have survived for a long time following MeHg administration.…”
Section: Fumiaki Mori Kunikazu Tanji and Koichi Wakabayashimentioning
confidence: 99%
“…Some primates in the study of Garman et al., (1975) showed a similar distribution. It is possible that the granular layer neurones, which are known to be particularly sensitive to the toxic effects of methylmercury, (Carmichael, Cavanagh & Rodda 1975;Jacobs, Carmichael & Cavanagh, 1977;Cavanagh, 1977) succumbed to mercury concentrations that were below the detection limit of the staining technique used in this study. Alternatively, mercury in the larger neurones and glial cells may have undergone a chemical transformation essential for the precipitation of silver by the technique used or which prevents its loss from the cells during tissue preparation.…”
Section: Discussionmentioning
confidence: 95%
“…In man, sensory and motoric dysfunction including paresthesia, constriction of the visual field, impairment of fine coordination, and ataxia have been described (1 1-14). Similar neurological disturbances are found after administration of organomercurial compounds in the rat, rabbit, mink, and cat (15)(16)(17)(18). Histomorphologically, the earliest signs of experimental intoxication are dispersion of rough endoplasmic reticulum in neurons (19), followed by diminished protein synthesis in the same cells (20).…”
mentioning
confidence: 51%
“…Histomorphologically, the earliest signs of experimental intoxication are dispersion of rough endoplasmic reticulum in neurons (19), followed by diminished protein synthesis in the same cells (20). Later, degenerative and necrotic changes are seen, especially in primary sensory ganglion cells and in Purkinje and granule cells of the cerebellum (15,18).…”
mentioning
confidence: 97%